Analisis Dan Perancangan Sistem Informasi Penilaian Harga Perolehan Barang Dagang Dengan Metode Moving Average - Qudratul Nurjanah, Agustin (METIK JURNAL (AKREDITASI SINTA 3), 2023)
The Indrayana Jaya Outdoors store requires an accurate and timely information system for the valuation of the purchase price of merchandise so that the flow of information needed runs as expected. The method of determining the moving average price (Moving Average), the acquisition price is not carried out at the end of the period, but at every purchase transaction. The results of the problem analysis found many things that caused the goals of the system not to be achieved. In knowing the information on the inventory of merchandise in the warehouse, it takes a duration of more than 10 minutes because you must first find and collect the required data one by one. Recording data that is still in handwriting or using working papers also hinders officers from finding the information needed because the document is not legible or multiple writing errors are made. As well as to determine the selling price, the purchase price of the goods is only an estimate, so the possibility of receiving only a small profit. By using the Moving Average Method, Indrayana Jaya Outdoors Stores can process data and present information on the acquisition price of merchandise accurately and on time.